2015
DOI: 10.1021/acs.jpcc.5b05958
|View full text |Cite
|
Sign up to set email alerts
|

XPS Analysis of the Surface Chemistry and Interfacial Bonding of Barrier-Type Cr(VI)-Free Anodic Oxides

Abstract: In the transition to environmental friendly pretreatment of aerospace aluminum alloys, chromic acid anodizing (CAA) is being replaced by sulfuric acid (SAA), phosphoric acid (PAA) or phosphoric-sulfuric acid (PSA) anodizing. While generally the main concern is controlling the film morphology, such as the pore diameter, oxide-, and barrier layer thickness, little is known on how the anodic oxide chemistry affects the interactions at the interface upon adhesive bonding. To study the link between surface chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 40 publications
(96 reference statements)
1
63
0
Order By: Relevance
“…Conversely, sulfur concentration is relatively constant in both measurements. These observations are in agreement with earlier in-depth study performed using Auger electron spectroscopy (AES) 7 . As oxide hydration is mostly dominant close to the surface, oxides other than SAA and PAA exhibit a higher hydroxyl fraction at θ =15° 42, 43 .…”
Section: Oxide Chemical Characterizationsupporting
confidence: 93%
See 2 more Smart Citations
“…Conversely, sulfur concentration is relatively constant in both measurements. These observations are in agreement with earlier in-depth study performed using Auger electron spectroscopy (AES) 7 . As oxide hydration is mostly dominant close to the surface, oxides other than SAA and PAA exhibit a higher hydroxyl fraction at θ =15° 42, 43 .…”
Section: Oxide Chemical Characterizationsupporting
confidence: 93%
“…Currently, different electrolytes are typically mixed in the anodizing bath to create the conditions that will result in film features similar to CAA anodic oxides. Some examples include boric-sulfuric acid anodizing (BSA) 4 , phosphoric acid modified boric-sulfuric and anodizing 5 , tartaric-sulfuric acid anodizing (TSA) 6 and phosphoric and sulfuric acid (PSA) anodizing 7 . In this paper, we focus on the latter option being the prime Cr(VI)-free candidate for bonded components that will serve as part of the loadcarrying primary aircraft structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the density of hydroxyl groups at the surface of SAA oxide is larger than for PSA oxides (approximately double, depending on the anodizing conditions). 12 Therefore, higher peel strengths can be achieved with less surface area and performance differences can be related to changes in the oxide chemistry, as illustrated in Fig. 5d.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5a-d all show an oxide at the interface, which is the anodised coating. S was detected in this layer, presumably due to the incorporation of SO 4 2− ions from the anodising process ( Figure 5c) [57].…”
Section: Sem/edsmentioning
confidence: 99%